Penguatan Pemahaman Transisi PAUD-SD Bagi Orang Tua Di TK Raushan Fikra - Nur Raoda Sari; Angri Lismayani; Nur Alim Amri (Universitas Negeri Makassar, 2023)
The strengthening of the PAUD-SD transition requires a collaborative effort from various parties with their respective roles ranging from parents/guardians, teachers, and also the government. As teachers and parents, it is very important to understand the PAUD-SD transition process because it will jointly build children's foundation abilities holistically and gradually since they are at the PAUD level. There are still many parents who do not understand their role in strengthening the PAUD-SD transition and there are still many parents who understand the information that PAUD should not foster literacy and numeracy, while entering primary school education, a calistung test is applied as part of the admission of new students. In addition, parents also understand that learning practices in PAUD are inconsistent, with some PAUD units focusing heavily on literacy skills and memorization, while others are completely anti-pursuit. Based on this phenomenon, the solution offered for this problem is to carry out a parenting program on the role of parents in strengthening a pleasant PAUD-SD Transition. The purpose of this activity is for parents to understand their role in strengthening the PAUD SD transition. The methods for implementing this activity are: (1) Conduct a situation analysis by conducting a dialogue with parents regarding what is done to support children entering elementary school; (2) Design a mentoring program to provide knowledge for parents; (3) Implement Parenting Seminar activities; and (4) Evaluate activities by conducting joint reflections. The result of this activity is that parents understand what parents should do that economic readiness alone is not enough in preparing children to enter elementary school, but must support children from fostering curiosity, emotional development, language use, cognitive development, and general knowledge.